PENYULUHAN BULLYING DAN KEKERASAN PADA ANAK DAN REMAJA: UPAYA PENCEGAHAN MELALUI EDUKASI KESEHATAN MENTAL DI RT 25 KELURAHAN SAWAH LEBAR BARU - Andra Saferi Wijaya; Septiyanti; Andara Meilia Selviana; Dyah Endang Kusuma (Poltekkes Kemenkes Bengkulu, 2026)
Bullying is one of the significant social problems among children and adolescents with serious impacts on mental health and emotional development. In Indonesia, bullying cases are still quite high and often occur in school and community environments. Lack of understanding about the impact of bullying and minimal prevention education programs are factors that exacerbate this situation. The purpose of this community service is to increase children and adolescents' knowledge about bullying and violence and provide prevention strategies that can be applied in daily life. The target of community service is children and adolescents in RT 25 Sawah Lebar Baru Village, totaling 34 people. This service begins with socialization about the definition, types, causes, and prevention strategies of bullying and measuring the increase in target knowledge from the counseling that has been given. The implementation method uses lecture and question-and-answer approaches with LCD media, power point, and leaflets. The results of community service showed an increase in knowledge of 98.1% from before and after counseling was given. Children and adolescents also showed high enthusiasm in participating in activities and were able to understand the importance of preventing bullying behavior in their environment.